2012
DOI: 10.1155/2012/321406
|View full text |Cite
|
Sign up to set email alerts
|

L-DOPA Uptake in Astrocytic Endfeet Enwrapping Blood Vessels in Rat Brain

Abstract: Astrocyte endfeet surround brain blood vessels and can play a role in the delivery of therapeutic drugs for Parkinson's disease. However, there is no previous evidence of the presence of LAT transporter for L-DOPA in brain astrocytes except in culture. Using systemic L-DOPA administration and a combination of patch clamp, histochemistry and confocal microscopy we found that L-DOPA is accumulated mainly in astrocyte cell bodies, astrocytic endfeet surrounding blood vessels, and pericytes. In brain slices: (1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…However, as chronic L-DOPA administration does not restore the SWM deficit, as shown in this study, the question remains as to which would be the mechanism involved in the exacerbation of the SWM deficit induced by L-DOPA. The therapeutic effect of L-DOPA is conditioned through decarboxylation and thus transformed into DA; however, if unregulated this process could also be the mechanism which induces toxicity. The excessive DA produced by L-DOPA administration can be generated by several types of cell as well as by remaining dopaminergic neurons, with some reports showing that both serotonergic neurons (Arai et al, 1995;Tanaka et al, 1999) and astrocytes can release DA from exogenous L-DOPA (Inyushin et al, 2012) in models of PD. The main event that enhances the release of DA is serotonergic sprouting, which occurs after an intra-nigral 6-OHDA lesion (Zhou et al, 1991;Parent et al, 2011), thus offsetting the dopaminergic denervation.…”
Section: Discussionmentioning
confidence: 99%
“…However, as chronic L-DOPA administration does not restore the SWM deficit, as shown in this study, the question remains as to which would be the mechanism involved in the exacerbation of the SWM deficit induced by L-DOPA. The therapeutic effect of L-DOPA is conditioned through decarboxylation and thus transformed into DA; however, if unregulated this process could also be the mechanism which induces toxicity. The excessive DA produced by L-DOPA administration can be generated by several types of cell as well as by remaining dopaminergic neurons, with some reports showing that both serotonergic neurons (Arai et al, 1995;Tanaka et al, 1999) and astrocytes can release DA from exogenous L-DOPA (Inyushin et al, 2012) in models of PD. The main event that enhances the release of DA is serotonergic sprouting, which occurs after an intra-nigral 6-OHDA lesion (Zhou et al, 1991;Parent et al, 2011), thus offsetting the dopaminergic denervation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that oxidative stress can affect the glial cells (astrocytes and microglia), which play a complex role in dopaminergic neurotoxicity [4]. Both microglia and astrocytes can degrade dopamine with the subsequent generation of oxidative stress and detrimental effects on dopaminergic neurons [5]. In addition, astrocytes appear to be important regulators of the inflammatory events that occur in stroke [6].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, neutral amino acid transporter (LAT) and DA transporter (DAT) are expressed in cortical and hippocampal astrocytes [11], [12], [13], [14], [15]. Based on the above background, we postulated that the uptake and metabolism of L-DOPA and DA in striatal astrocytes influences their availability in the dopaminergic system of PD patients.…”
Section: Introductionmentioning
confidence: 99%